Optimasi Gasifikasi Serbuk Tandan Kosong Kelapa Sawit Menggunakan Powder Gasifier Type Cyclone - Riksa Prayogi Widyaprawira; Radi Radi; Bambang Purwantana (agriTECH, 2019)
Every year, palm-oil production is increasing. Each ton of fresh fruit bunches produced to 22%–23% of oil palm empty fruit bunches (OPEFB). Based on the laboratory test, OPEFB contains 69,72% volatile and 3353,97 kcal/kg of calor. Aim of the research is to determine size material OPEFB in gasification process, determine combination AFR (Air Fuel Ratio) in gasifier tipe cyclone so that produce optimal energy and to prediction gasification process with CFD method (Computational Fluid Dynamic). The powder gasifier cyclone type method is used to convert this into renewable energy. The research method consists of OPEFB powder material with 14, 30 and 50 mesh treatment, 4 air-fuel ratio, and material mass rate treatments, and variations of the length of middle-pipe treatment. The weight of each sample is 500 g, added with 100 g of charcoal and repeated 3 times. The result shows the mesh A3 has the highest temperature at 348.23 °C, 1008,68 kcal/kg of heat value, 30.07% of efficiency, 97.81 kg/kg of AFR value, but has the lowest engine working capacity (EWC) with 14.65 kg/hours. Based on sensor test, A3 treatment, the voltage of monoxide sensor output is 1.45 mV; 1.81 mV of hydrogen; and methane at 0.66 mV. In the combination of air speed and screw rotational treatment, AFR values were generated by treatment B4 with EWC value of 20 kg/hour and AFR of 97.1 kg/kg. The highest gasmonoxide sensor results in treatment B4 is 1.58 mV; hydrogen 1.98 mV. Based on the length of the enter pipe in the reactor, treatment C1 produces an optimal value of the EWC value at 16.6 kg/hour, the heat energy value is 997 kcal/kg, the efficiency value is 29.73% and the AFR value is 82,87 kg/kg. In treatment C1 the gas monoxide sensor voltage is 1.6 mV; and methane is 1.46 mV. The CFD simulation shows that the distribution of temperature, fluid velocity and pressure in the middle iteration have a significant increase. This can be influenced by the dimensions of powder gasifier cyclone type with CFD simulation.